Longitudinal links between maternal factors and infant cognition: Moderation by infant sleep. (6th January 2020) - Camerota, Marie; Gueron‐Sela, Noa; Grimes, Melissa; Propper, Cathi B.
Abstract: The current study examined the moderating role of infant sleep in the link between maternal factors (i.e., maternal education, depressive symptoms, sleep disturbance) and infant cognition. Data come from 95 African American parent–child dyads. At 3 months of age, infant sleep was objectively measured using videosomnography and actigraphy, from which measures of sleep regulation and consolidation were calculated. Mothers also self‐reported their level of education, depressive symptoms, and sleep quality. At 6 months of age, infants completed cognitive assessments, including a measure of general cognitive ability and observed attention behavior. Findings revealed that infant sleep quality interacted with maternal education and sleep disturbances to predict cognition. Specifically, the link between maternal education and infants' attention behavior was significant and positive for infants with better regulated sleep, but not for infants with poorly regulated sleep. Similarly, the link between maternal sleep disturbance and infant cognition depended on infant sleep quality. For infants with poorer sleep consolidation, increased maternal sleep disturbance predicted poorer infant general cognitive ability. For infants with better sleep consolidation, maternal sleep disturbance was positively related to both general cognitive ability and attention behavior. These findings suggest that infant sleep quality moderates the impact of environmental factors on cognitive functioning.